Comparative study on the effects of Acacia albida on yield and yield components of different cereal crops in Southern Ethiopia - Getahun Haile; Mulugeta Lemenih; Fisseha Itanna; Getachew Agegnehu (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2021)
We studied the effects of Acacia albida on the growth and yield of wheat, maize, and teff with increasing distance from trees in Ethiopia in the 2014/2015 cropping season. The treatments comprised four radial distances of 1.5m, 3.5m, 5.5m, and 12.5m as a control away from the tree with three replications. Results showed that higher wheat yields were recorded at 5.5m and 3.5m than at 12.5m, with yield increments of 11 and 12%, respectively compared to 12.5m. The highest maize yield was obtained from 3.5m, with a yield advantage of 12.3% compared to 12.5m. Teff yield increased with increasing distance from the tree trunk. Wheat and maize yield gains near the canopies may be associated with higher organic matter and soil nutrients, while their yield reduction with decreasing distance from the tree may be associated with the shading effect of tree canopies. Wheat was the most compatible crop when integrated with A. albida under shade conditions followed by maize, while teff was highly susceptible to shading effect. We suggest that integrating A. albida with the right crops and appropriate tree management could enhance crop yield. Lopping is required before sowing teff and maize with A. albida to minimize shading effects